Neurological Physical Therapy 2017
DOI: 10.5772/67470
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Motor Imagery After a Variety of Motor Learning Times on Excitability of Spinal Motor Neurons and Accurate Motion

Abstract: Purpose: This study aimed to examine the effects of motor imagery on the excitability of spinal motor neurons and accurate motion. Subjects and Methods: About 30 healthy volunteers were recruited. F-waves were recorded at rest, while touching a sensor and motor imagery conditions. Also, the pinch force was measured before and after motor imagery. Furthermore, the subjects mastered the 50% MVC pinch force with learning times of 10 s, 30 s, 1 min, and 2 min beforehand. Results: Spinal motor neuron excitability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Due to this reason, we thought that motor imagery was maintaining motor accuracy. The differences point on this study and our previous study [13] was majority subject improvement motor accuracy. It is considered that intermittent motor learning was to increase the motor imagery effect than consecutive.…”
Section: Appropriate Motor Practice Methods Before Motor Imagery? 41 contrasting
confidence: 85%
See 3 more Smart Citations
“…Due to this reason, we thought that motor imagery was maintaining motor accuracy. The differences point on this study and our previous study [13] was majority subject improvement motor accuracy. It is considered that intermittent motor learning was to increase the motor imagery effect than consecutive.…”
Section: Appropriate Motor Practice Methods Before Motor Imagery? 41 contrasting
confidence: 85%
“…Our previous study [13] reported that the motor imagery after motor learning with consecutive using visual feedback was to maintain the motor accuracy. And, Heuer and Hegele [17] reported that the motor learning with intermittent using visual feedback was effective than consecutive.…”
Section: Appropriate Motor Practice Methods Before Motor Imagery? 41 mentioning
confidence: 99%
See 2 more Smart Citations